Analisis Masalah Spiritual Care pada Pasien - Nurul Jamil; Nurul Hidayah; Nisma; Fajar Yousriatin (MES Bogor, 2025)
Spiritual Care is an aspect that cannot be separated from the holistic nursing care process. However, until now, spiritual care has not been prioritized, even though spiritual problems have been proven to support the patient's healing process. This condition needs to be followed up, one of which is by continuously analyzing the situation. This research aims to Describe problems that generally occur in the process of Spiritual Care. Researchers used quantitative descriptive research methods. The sample in this research consisted of only 11 samples, with a total sampling technique. Researchers experienced limitations, considering several potential respondents were currently in the educational process. The results of the research show that there are specific variables that hinder the optimization of Spiritual Care, namely the time that nurses have, the patient's awareness, and the lack of training related to Spiritual Care. The author concludes that there is a need for better support with Spiritual Care management. Innovative approaches also need to be given to patients, to increase their awareness.